The Profitability analyses of crop production enterprises in Hajdú-Bihar county, especially in Hajdúböszörmény - Erdős, Adél Dorottya; Szőllősi, László (Studia Mundi – Economica, 2021)
In Hungary agriculture has a prominent role in terms of raw material production. Crop production representing the highest proportion of it and support policy prioritizes it also. In our country there are many counties, where outstanding conditions (good soil quality, favourable weather conditions, arable land with a high golden crown value) are for producing crop. One of the most significant county is Hajdú-Bihar, where 325 thousand hectares arable land are. 8 percent of this area is used by enterprises in Hajdúböszörmény. During our research secondary data were used from HCSO (national and county data specific to agriculture) and EMIS database (report details of enterprises). In the examined 853 Hungarian enterprises farms of Hajdú-Bihar County and of Hajdúböszörmény were payed special attention. Based on value of operating ROS, ROE and ROI both farms of county and Hajdúböszörmény produce profitable, however their farm size were different. The enterprises in Hajdúböszörmény had favourable situation based on operating ROS (12,57%) compared to national (5,30%) and county (8,90%) average values. All of this can be explained by the higher fixed assets value and rate for the period 2015-2019. Behind this more advanced technology are presumed.